METHODS OF DIAGNOSIS EARLY STAGE OF PARKINSON'S DISEASE (World Bulletin of Public Health, 2023)
In recent years, due to the increasing elderly population in developed countries, there has been a steady increase in neurodegenerative diseases, which include Parkinson's disease (PD). The prevalence of PD ranges from 100 to 300 people per 100,000 population. In the age group older than 65 years, the prevalence is higher, ranging from 1,280 to 1,500 per 100,000 population